1998
DOI: 10.1520/jfs16218j
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Thickness in American Females and Males

Abstract: To date, numerous studies have examined the range of cranial thickness variation in modern humans. The purpose of this investigation is to present a new method that would be easier to replicate, and to examine sex and age variation in cranial thickness in a white sample. The method consists of excising four cranial segments from the frontal and parietal regions. The sample consists of 165 specimens collected at autopsy and 15 calvarial specimens. An increase in cranial thickness with age was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 7 publications
5
62
1
3
Order By: Relevance
“…During brain development, internal pressure from expanding brain parenchyma creates outward tensional forces on the pliable cranial bones and sutures, thus inducing cranial expansion (Sperber et al, 2001). Researchers have disputed the relationship between age, cranial bone thickness, and cranial volume in later life (Anderson, 1882;Getz, 1961;Lynnerup, 2001;Ross et al, 1976Ross et al, , 1998Todd, 1924). This disagreement arises from two antagonistic forces acting on the skull: the first is bone loss occurring with age throughout the skeletal system.…”
mentioning
confidence: 99%
“…During brain development, internal pressure from expanding brain parenchyma creates outward tensional forces on the pliable cranial bones and sutures, thus inducing cranial expansion (Sperber et al, 2001). Researchers have disputed the relationship between age, cranial bone thickness, and cranial volume in later life (Anderson, 1882;Getz, 1961;Lynnerup, 2001;Ross et al, 1976Ross et al, , 1998Todd, 1924). This disagreement arises from two antagonistic forces acting on the skull: the first is bone loss occurring with age throughout the skeletal system.…”
mentioning
confidence: 99%
“…5 Ross AH et.al had done research on cranial thickness in American females and males with an objective to examine sex and age variation in cranial thickness in a White sample.An increase in cranial thickness with age was observed and there was no statistical difference in calvarial thickness between male and female. 6 Contrary to the Ross et.al finding,,Hatipoglu HG et.al found sexual dimorphism in all craniometric data observed positive correlation between body mass index and diploeic thickness. 7 Hwang K et.al carried out thickness mapping of the parietal bone in Korean adults and concluded that the parietal bone tended to be thicker towards the Lamda point than at the coronal suture area.…”
Section: Discussionmentioning
confidence: 66%
“…The research results analyzing the relationship between cranium thickness and sex are contradictory, as well (Hwang et al;Ross et al;Lynnerup;Ishida & Dodo, 1990;Smith et al, 1985;Getz, 1960). Hwang et al, found the average parietal bone thickness to be 7.31 ± 1.6 mm in women, 6.43 ± 1.6 mm in men, and average lamina externa thickness to be 2.01 ± 0.7 mm in women, 1.86 ± 0.7 in men.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the researchers putting forward that morphologic and morphometric changes occur with aging in cranium, there are some other researchers claiming that diploic composition does not change (Hwang et al;Skrzat et al, 2004;Sullivan & Smith, 1989;Ross et al, 1998).…”
Section: Introductionmentioning
confidence: 99%